Excision Repair Cross Complementation Group 1 Single Nucleotide Polymorphisms and Nivolumab in Advanced Non-Small Cell Lung Cancer - Aiello, Marco Maria; Solinas, Cinzia; Santoni, Matteo; Battelli, Nicola; Restuccia, Nunzio; Latteri, Fiorenza; Paratore, Sabrina; Verderame, Francesco; Albanese, Giuseppina Valeria; Bruzzi, Paolo; Soto Parra, Hector Josè (Frontiers in Oncology, 2020)
Background We hypothesized that Non-Small Cell Lung Cancer (NSCLC) patients with tumor positive for single nucleotide polymorphisms (SNPs) of the Excision Repair Cross Complementation Group 1 (ERCC-1) gene could be more genetically instable and consequently more responsive to Programmed Death 1 (PD-1) blockade. Methods We evaluated the T19007C and C8092A ERCC-1 SNPs by pyrosequencing assay on tumor specimens from two independent cohorts of patients who relapsed after one or more prior systemic treatments for advanced NSCLC and received nivolumab (3 mg/kg intravenously every 2 weeks) as part of the Expanded Access Program. We aimed to assess the outcome of enrolled subjects according to the ERCC-1 SNPs status, in order to evaluate the role of these polymorphisms as predictive biomarkers of response/clinical benefit to anti-PD-1 therapies. Results Of the 45 patients included in the final analysis, 21 (47%) and 16 (36%) patients were positive for the T19007C and C8092A polymorphic genotype (PG), respectively. In univariate analyses, OS and PFS were shorter in patients with the T19007C PG but neither difference achieved statistical significance (P=0.131 and P=0.717, respectively). The presence of the C8092A PG was associated both with a longer OS and PFS although only PFS was statistically significant (P=0.112 and P=0.025, respectively). These results were confirmed in multivariate analyses. The response rate was significantly higher only in patients with the C8092A PG than wild-type patients (62% vs 7%, P<0.001). Conclusions Results from this pilot study provided suggestive evidences that a subgroup of NSCLC patients could benefit differently from nivolumab according to the C8092A ERCC-1 SNP status. These data warrant further investigation.